An experimental assisted mathematical modeling to study the desorption capacity of the clay based solid desiccant - Mohanram Parthiban; Venkatesh Chenrayan; Chandraprabhu Venkatachalam; Kiran Shahapurkar; Addisu Bekele (Materials Research Express, 2021)
Since the moisture present in the vegetables and fruits are initially more, they are endangered to spoil quickly. The ability of the desiccant materials to absorb moisture can be used for drying. By incorporating desiccants in the drying process, drying can also be carried out during no sunshine periods. The absorbed moisture can be desorbed by passing hot air stream through the desiccants. A cylindrical desiccant mould with varying diameters of concentric holes, comprising of vermiculite (20%), bentonite (60%), cement (10%) and calcium chloride (10%) has been prepared. The sizes of the concentric holes were made in three different diameters as 6, 12 and 18 mm. Different mass flow rates and temperatures were followed to conduct the experiment as per Box- Benhen design. The ANOVA analysis was performed to arrive the percentage of contribution of influence over the desorption. Various indicators including the percentage of error between measured and predicted responses were employed to uphold the accuracy of the proposed mathematical model. The extensive statistical study reveals that the 6 mm of hole diameter, 0.003 Kg m ^−2 s of mass flow rate and 60 °C temperature are the optimal parameters for the solid desiccant to regenerate effectively.